PENGGUNAAN METAFORA VISUAL DALAM FILM “TENGGELAMNYA KAPAL VAN DER WIJCK”: ANALISIS SEMIOTIKA - Agung, Muhammad; Usman, Usman; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the use of visual metaphors in the film Tenggelamnya Kapal Van Der Wijck through the semiotic approach of Charles Sanders Peirce, revealing the messages embedded within these metaphors while classifying them into five categories as proposed by Noël Carroll: Potrait Komposit, composite construction, Fotomontase, animation category, and superimposition. The research method used is qualitative, with data consisting of visual elements from the film Tenggelamnya Kapal Van Der Wijck, directed by Sunil Soraya and adapted from the novel by Buya Hamka. Data analysis follows the Miles and Huberman model: data reduction, data display, and conclusion drawing. The findings consist of visual metaphors analyzed using Peirce's triadic sign model (representamen, object, interpretant), uncovering symbolic meanings that enrich the film’s narrative while also identifying the type of visual metaphor. The results show that four out of the five types of visual metaphors appear in the film. This research contributes to a deeper understanding of cinema’s power to convey messages and emotions through visual storytelling